Повышение эффективности ультразвукового контроля пеналов хранения ОЯТ; Известия вузов. Физика; Т. 61, № 9, ч. 2 - Абрамец В. В. Владислава Владимировна; Салчак Я. А. Яна Алексеевна; Седнев Д. А. Дмитрий Андреевич; Мацеля В. И. Владимир Иванович; Сеелев И. Н. Игорь Николаевич (2017, 2017)
Заглавие с экрана